Effect of layered geological structures on borehole heat transfer. (March 2021) - Karabetoglu, Sevan; Ozturk, Z. Fatih; Kaslilar, Ayse; Juhlin, Christopher; Sisman, Altug
Highlights: Influence of geological structures on borehole performance. Statistical characteristics of geo-structures and deviations from homogeneous model. Performance predictions of a deep borehole in a layered geological structure. Comparison of layered and homogeneous model predictions. Analytical derivation for the deviations from homogeneous model. Abstract: Borehole heat exchangers, especially deep ones, are usually drilled through different geological layers having varying properties. Homogeneous and layered models can be used for borehole performance predictions. The homogeneous model considers all layers as a single layer having effective properties while the layered model considers all layers separately and gives better accuracy, although it is more complicated and time consuming to calculate. In this study, by considering real geological structures, thermal performance predictions of a deep borehole are made using both homogeneous and layered models and the results are compared to examine how predictions differ from each other depending on the statistical characteristics of geological structures. An analytical expression is derived for the relation between statistical characteristics and deviations from the predictions of the homogeneous model. The magnitudes of deviations are very small and essentially depend on the variance of the difference for the thermal properties of the layers and a time decaying function. The results help to understand how horizontally layered geological structures influence borehole performance and when we need a layered model.